Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/ijo.2018.4477
|View full text |Cite
|
Sign up to set email alerts
|

NT21MP negatively regulates paclitaxel-resistant cells by targeting miR‑155‑3p and miR‑155-5p via the CXCR4 pathway in breast cancer

Abstract: Evidence has shown that microRNAs (miRNAs) are vital in cell growth, migration, and invasion by inhibiting their target genes. A previous study demonstrated that miRNA (miR)-155-3p and miR-155-5p exerted opposite effects on cell proliferation, apoptosis, migration and invasion in breast cancer cell lines. An miRNA microarray was used to show that miR-155-3p was downregulated whereas miR-155-5p was upregulated in paclitaxel-resistant (PR) cells compared with parental breast cancer cells. However, the role of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
2
9
1
Order By: Relevance
“…Furthermore, miR-155 directly targeted and inhibited a series of genes (e.g. FOXO3, SMARCA4 or Ubiquilin-1) to participate in the biological process of tumor development (37)(38)(39)(40). To the best of our knowledge, the present study was the first to indicate that TERF1 may be a direct target of miR-155, as confirmed by a dual luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, miR-155 directly targeted and inhibited a series of genes (e.g. FOXO3, SMARCA4 or Ubiquilin-1) to participate in the biological process of tumor development (37)(38)(39)(40). To the best of our knowledge, the present study was the first to indicate that TERF1 may be a direct target of miR-155, as confirmed by a dual luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have found that microRNA-155 is abnormally expressed in various tumors and plays a centrol role in the process of tumor initiation, progression, invasion, and metastasis [29][30][31][32][33][34][35] . Our results indicated that expression of microRNA-155 can be up-regulated in some patients of gastric cancer and down-regulated in others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that microRNA-155 is abnormally expressed in various tumors and plays a centrol role in the process of tumor initiation, progression, invasion, and metastasis [29][30][31][32][33][34][35] . Our results indicated that expression of microRNA-155 can be up-regulated in some patients of gastric cancer and down-regulated in others.…”
Section: Discussionmentioning
confidence: 99%